2020
DOI: 10.1016/j.toxrep.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of biological activity of Tragopogon porrifolius and Polygonum cognatum consumed intensively by people in Sivas

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…Using this program, ranges matching 95% of known drugs are taken into account and the properties of a particular molecule are predicted. Qik-Prop also includes values similar to Lipinski rules: MW (130.0-725.0), octanol/water partition coefficient log P (−2-6.5), number of HBDs (0-6), number of hydrogen bond acceptors (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Compounds that satisfy these rules are considered druglike.…”
Section: The Results Of In Silico Analysesmentioning
confidence: 99%
“…Using this program, ranges matching 95% of known drugs are taken into account and the properties of a particular molecule are predicted. Qik-Prop also includes values similar to Lipinski rules: MW (130.0-725.0), octanol/water partition coefficient log P (−2-6.5), number of HBDs (0-6), number of hydrogen bond acceptors (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Compounds that satisfy these rules are considered druglike.…”
Section: The Results Of In Silico Analysesmentioning
confidence: 99%
“…This enzyme can increase the blood sugar level, as hydrolyses (1,4)-α- d -glycosidic linkages in polysaccharides contain three or more (1,4)-α-linked D-glucose units. Another study demonstrated that the EtOH extract of P. cognatum strongly inhibited α-amylase activity (86.6%) and moderately inhibited α-glucosidase activity (41.05%) with respect to the standard acarbose (58.4% and 57.56%, respectively) [ 169 ].…”
Section: Pharmacological Activities Of Persicaria and Polygonum Products: Different Type Of Extractmentioning
confidence: 99%
“…Hücre canlılığı, 24-48 saatlik inkübasyondan sonra hücrelerin mitokondriyal aktivitesinin, oldukça hassas WST-1 deneyi ile tayin edilmesi suretiyle belirlendi (Boivin, Blanchette, Barrette, Moghrabi, & Beliveau, 2007). Negatif kontrol olarak DMEM (% 0,5 DMSO içerir) kullanıldı (Eruygur et al, 2020). WST-1 hücre proliferasyon deneyleri sonucunda IC50 değerleri GraphPad Prism 6 programı kullanılarak hesaplandı (SARAÇ et al).…”
Section: Hücre Kültürüunclassified